2018
DOI: 10.1002/jsfa.9044
|View full text |Cite
|
Sign up to set email alerts
|

New methods for high‐accuracy insect chitin measurement

Abstract: According to statistical analysis, ADF-ADL represents a compromise between accuracy and equipment demand and is a suitable method for determining the chitin content of both insects and their residues. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 18 publications
1
50
1
1
Order By: Relevance
“…In the present study, cadmium and arsenic were not found, and lead (3.6 mg/kg DM) was below the maximum limit of 10 mg/kg (88% DM) permitted by the EU [33]. The content of chitin in BSFL can be estimated by detergent fibre results (ADF−ADL = 6.60 g/100 g DM; [34]). Chitin has been associated with prebiotic and antimicrobial properties, although it may also be considered as an antinutritional factor when high content is included in the diet [5].…”
Section: Discussioncontrasting
confidence: 50%
“…In the present study, cadmium and arsenic were not found, and lead (3.6 mg/kg DM) was below the maximum limit of 10 mg/kg (88% DM) permitted by the EU [33]. The content of chitin in BSFL can be estimated by detergent fibre results (ADF−ADL = 6.60 g/100 g DM; [34]). Chitin has been associated with prebiotic and antimicrobial properties, although it may also be considered as an antinutritional factor when high content is included in the diet [5].…”
Section: Discussioncontrasting
confidence: 50%
“…However, considering the final chitin content of diets when substituting 50% of SBM with Hermetia meal, no major impact on pcD of CP can be expected. Nevertheless, there is also a lack of reliable information about the chitin content of insects according to invalid analytical procedures insufficiently taking the N fraction of chitin into account [64].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the chitin content of whole insects is generally lower. 78,85 Due to the moderate content, insect breeding only for chitin isolation is not economically feasible without cascade usage of other compounds derived from the insect breeding.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…75 H. illucens could be grown on a wide range of organic side streams and contributes to a circular economy. 76,77 Exoskeletons from H. illucens larvae contain up to 35% chitin, 78 which means that it is one of the main compounds that could be isolated from the byproducts of the insect farming industry. 73 Thus, chitin-rich byproducts from insect farming present a new and sustainable source of commercial chitin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation